ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA KEUANGAN PT. BERDIKARI UNITED LIVESTOCK - Andi Indra Martini (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The purposes of this reseach are : (1) to determine whether or not the amount of fixed assets, long term debt and equity in simultaneusly would affect the financial performances at Berdikari Livestock Limited; (2) to determine whether or not the amount of fixed assets, long term debt and equity, in partially would affect the financial performances at Berdikari Livestock Limited.